Swelling stress development in confined smectite clays through exposure to CO2. (July 2018) - Zhang, M.; de Jong, S.M.; Spiers, C.J.; Busch, A.; Wentinck, H.M.
Highlights: A self-stressing effect has been verified in confined smectites exposed to CO2 . Swelling stresses exerted by smectites due to CO2 uptake can reach several tens MPa. CO2 interaction with clayey caprocks can cause increment to in-situ stress components. Swelling and self-stressing effect are likely to enhance caprock sealing integrity. Abstract: Recent work has shown that unconfined smectite clays swell upon exposure to supercritical (SC) CO2 due to uptake in the clay interlayer region. Such swelling behaviour is expected to cause internal stress development under geometrically confined conditions pertaining to geological storage of CO2, but this has not been widely investigated. Here, we report uniaxial compaction/swelling tests performed, using a 1-D compaction cell, on pre-pressed discs of Wyoming (Na-SWy-1) and Arizona (Ca-SAz-1) montmorillonite, as well as on smectite-bearing shale. We explore the axial (Terzaghi) effective stress generated in these materials upon exposure to 10 MPa CO2 pressure under conditions where total swelling (including poroelastic effects) is restricted to axial strains below 3%. The experiments were performed at 44 °C. In each experiment, the sample was first equilibrated with lab air (RH ≈ 40%–60% at T = 20–25 °C) at the experimental temperature and pre-compacted at ∼60 MPa axial stress to generate a dense reproducible microstructure. A lower axial normal stress of 25.9–40.9 MPa was then applied and the loading piston held in fixed position. This yielded an effective (Terzaghi) overburden stress of 9.6–24.7 MPa upon introduction of CO2 at 10 MPa, thus simulating burial depths of ∼0.8–2.0 km. Following CO2 introduction, axial swelling stresses developed rapidly, independently of the direct effect of increased pore pressure, attaining values of 7.1–12.4 MPa at equilibrium, compared with ∼2 MPa obtained using inert Ar. Experiments on Na-SWy-1 montmorillonite showed that the swelling stress generated upon exposure to CO2 decreases with increasing initial and final effective normal stress, suggesting that overburden stress suppresses swelling (stress) development in smectite, presumably by limiting the amount of CO2 uptake by the material investigated. The swelling stresses observed imply that CO2 penetration into caprocks and faults in geological storage systems will lead to an increase in effective normal stress components, which in turn will tend to promote closure of fractures and enhance sealing integrity. However, further work is needed to improve understanding of the processes underlying the swelling of smectite caused by CO2 and to evaluate any risks posed to caprock and fault integrity by swelling-induced shear stresses.